Nghiên cứu cấu trúc, độ bền và khả năng hấp phụ khí CO của cluster Au3X(-1/0/1) (X = Sc, Y) - Cường, Nguyễn Quốc; Ngân, Vũ Thị; Trung, Nguyễn Tiến (Vietnam Journal of Chemistry, 2016)
Stable isomers of Au3X(-1/0/1) (X = Au, Sc, Y) clusters and fourteen stable geometries formed by the interaction of Au3X(-1/0/1) (X = Sc, Y) with CO were obtained at the BP86/LanL2DZ level of theory. All the most stable isomers of clusters examined prefer locating in low spin states. In general, the obtained results show that Au3Sc(-1/0/1) and        Au3Y(-1/0/1) clusters have similarities of structure and stability. It is remarkable that Au4- cluster is more stable than Au4+ and Au40 clusters. The stability of the complexes of CO and Au3X(-1/0/1) (X = Sc, Y) is contributed by s bonding (ss*(CO)® LUMO (cluster), p bonding (MO-dp (cluster)®pp*(CO)) and electrostatic interactions. When CO is absorbed by Au3X0 (X = Sc, Y) neutral clusters, charge factor plays a prominent role, while orbital factor has vital one in the cation complexes. Au atoms in the clusters prefer adsorption of C atom compared to O atom of CO molecule. Keywords. Density Functional Theory, scandium and yttrium-doped gold clusters, stable structure, adsorption